Mutagenicity and antimutagenicity of (-)-hinokinin a trypanosomicidal compound measured by Salmonella microsome and comet assays - Resende, Flavia Aparecida [UNESP]; Barbosa, Lilian Cristina; Tavares, Denise Crispim; de Camargo, Mariana Santoro [UNESP]; de Souza Rezende, Karen Cristina; de Andrade e Silva, Marcio Luis; Varanda, Eliana Aparecida [UNESP] (Biomed Central Ltd., 2012)
Background: The dibenzylbutyrolactone lignan (-)-hinokinin (HK) was derived by partial synthesis from (-)- cubebin, isolated from the dry seeds of the pepper, Piper cubeba. Considering the good trypanosomicidal activity of HK and recalling that natural products are promising starting points for the discovery of novel potentially therapeutic agents, the aim of the present study was to investigate the (anti) mutagenic/genotoxic activities of HK.Methods: The mutagenic/genotoxic activities were evaluated by the Ames test on Salmonella typhimurium strains TA98, TA97a, TA100 and TA102, and the comet assay, so as to assess the safe use of HK in the treatment of Chagas' disease. The antimutagenic /antigenotoxic potential of HK were also tested against the mutagenicity of a variety of direct and indirect acting mutagens, such as 4- nitro-o-phenylenediamine (NOPD), sodium azide (SA), mitomycin C (MMC), benzo[a] pyrene (B[a] P), aflatoxin B-1 (AFB(1)), 2-aminoanthracene (2-AA) and 2-aminofluorene (2-AF), by the Ames test, and doxorubicin (DXR) by the comet assay.Results: The mutagenicity/genotoxicity tests showed that HK did not induce any increase in the number of revertants or extent of DNA damage, demonstrating the absence of mutagenic and genotoxic activities. on the other hand, the results on the antimutagenic potential of HK showed a strong inhibitory effect against some direct and indirect-acting mutagens.Conclusions: Regarding the use of HK as an antichagasic drug, the absence of mutagenic effects in animal cell and bacterial systems is encouraging. In addition, HK may be a new potential antigenotoxic /antimutagenic agent from natural sources. However, the protective activity of HK is not general and varies with the type of DNA damage-inducing agent used.
Keywords: Hinokinin; Ames test; Comet assay; Mutagenicity; Antimutagenicity